(untitled) (Journal of the College of Basic Education, 2026)
This reserch, presented under the title (The Social and Artistic Biography of the Composer Farouk Hilal), aims to reveal the social and artistic biography of the Iraqi composer Farouk Hilal and to preserve his biography and works from extinction. The research included in its first chaptar To put the justifications that shed light on the necessity of studying the artist’s biography since the previous one did not address it, then the aim of the research, the importance and the limits that are determined by revealing (The Social and Artistic Biography of the Artist Farouk Hilal), In the second chapter (the theoretical framework), the researcher relied on two basic topics, (Iraqi Song) and (His Life and Works), and in view of the indicators and aspects that the theoretical framework revealed, the researcher prepared her analytical tool (5 questions) in the form of an interview After its presentation and validation by specialists, the researcher determined the research methodology (historical methodology) and determined the research community and sample, which were represented by the artist (Farouk Hilal). Then the researcher conducted the interviews and analyzed the answers and discussed them in the fourth chapter, and the results and conclusions became clear about the secret and reason for the distinction of this artist’s style from his peers. This was in (Chapter Five) by agreeing on several main points that were consistent with the research objective of revealing the artist’s biography. The researcher reinforced the conclusions with recommendations and suggestions and finally a list of sources